Hypercholesterolaemia treated by soybean protein diet. Issue 3 (March 1987) - Gaddi, A; Descovich, G C; Noseda, G; Fragiacomo, C; Nicolini, A; Montanari, G; Vanetti, G; Sirtori, M; Gatti, E; Sirtori, C R
Abstract : After a period of stabilisation on a controlled low lipid low cholesterol diet with animal proteins a group of 16 children with familial hypercholesterolaemia were given a textured soybean protein based diet, with a similar fat composition. All the children had a highly significant reduction in total cholesterol, averaging -21.8% against the baseline after eight weeks. Compliance became less strict afterwards, but more than half of the patients have regularly continued the diet and results have been maintained for one year. Minimal changes were noted in triglyceridaemia and in high density lipoprotein cholesterol concentrations, which showed a slight rise only at the end of treatment. The children's growth during the trial was normal. In view of the psychological difficulties of prescribing treatment with drugs to children with severe hypercholesterolaemia before puberty and of the relative ineffectiveness of standard low lipid diets in this condition the soybean protein diet may offer a satisfactory alternative.